2013
DOI: 10.1080/00288233.2013.809775
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus response and efficiency of four adventive annual clovers grown in a New Zealand high country soil under glasshouse conditions

Abstract: Maintaining and increasing legume abundance is a critical component of pastoral intensification, increasing nitrogen inputs to nitrogen deficient New Zealand high and hill country pastures and improving feed quality. Establishment and persistence of traditionally sown legume species white clover (Trifolium repens) and subterranean clover (T. subterraneum) is often limited in summer-dry high country. In contrast, naturalized, adventive annual pasture legume species such as cluster clover (T. glomeratum), haresf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
2
13
1
Order By: Relevance
“…The naturalised clovers T. campestre, T. glomeratum, and T. dubium had critical external P requirements similar to subterranean clover but a lower growth potential. This concurs with Maxwell et al (2013), who found that under both low-and high-P conditions the yield of T. subterraneum exceeded that of T. glomeratum, T. dubium and T. striatum. The native grasses A. scabra and R. caespitosum had the lowest critical values in the field experiment, but were of low nutrient value as livestock feed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The naturalised clovers T. campestre, T. glomeratum, and T. dubium had critical external P requirements similar to subterranean clover but a lower growth potential. This concurs with Maxwell et al (2013), who found that under both low-and high-P conditions the yield of T. subterraneum exceeded that of T. glomeratum, T. dubium and T. striatum. The native grasses A. scabra and R. caespitosum had the lowest critical values in the field experiment, but were of low nutrient value as livestock feed.…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence of considerable variation in plant response to increased fertility both between and within species (e.g. Gourley et al 1993;Hill et al 2010;Maxwell et al 2013;Haling et al 2016aHaling et al , 2016bHaling et al , 2018. The largest differences are in growth potential under non-limiting nutrition, but there are also differences in the critical P level at which 90% of maximum yield is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The soil Olsen P at which maximum yield was achieved differed substantially between legume species, but values were high in all cases. Species differences were likely driven by genetic adaptations to low phosphorus environments (Maxwell et al, 2013) and therefore each have different P requirements and P use efficiencies for growth (Raven et al 1992, Syers et al 2008). Tagasaste and 'Nomad' white clover peaked at the lowest Olsen P's, while Lucerne and balansa and white clover required very high Olsen P for peak yield.…”
Section: Phosphorus Responses and Critical P Requirementsmentioning
confidence: 99%
“…Key factors driving the presence of legumes in the field include soil fertility and moisture availability Moot 2010, 2014). Soil phosphorus (P) and pH are often low in dryland, both of which have negative impacts on pasture legumes (Maxwell et al 2013). However, very little information exists in literature on P efficient and pH tolerant legumes which may provide alternatives to white clover.…”
Section: Introductionmentioning
confidence: 99%
“…Trifolium repens, the commonly known and used clover species in permanent grasslands of the temperate zone (Käding and Werner 2003) and our most dominating legume species, was found to require P application rates of 200-250 mg P kg −1 soil to attain 97% of maximum yields in pot experiments in New Zealand (Moir et al 2012). This resulted in P Olsen concentrations of 46-78 mg kg −1 at the end of the study (Maxwell et al 2013). Davis (1991) calculated critical P concentrations in grassland legumes based on the optimal P concentrations for 90% of their maximum yields in a field study in New Zealand.…”
Section: Soil P and Legumesmentioning
confidence: 99%